2012
DOI: 10.15809/irriga.2012v1n01p368
|View full text |Cite
|
Sign up to set email alerts
|

Gotejadores Submetidos a Condições Críticas De Qualidade Da Água

Abstract: This work aims to quantify possible disturbances of flow rate in drip emitters subject to the application of potassium chloride, suspended solids, water containing organic material and concentrated solution of soluble iron. The experiment was accomplished in the Laboratory of Irrigation of the Department of Biosystem Engineering at ESALQ/USP, analyzing the performance of 22 drippers. All treatments had water with phytoplankton + 1 kg of clay soil, with applications of potassium chloride and positioning of emit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 9 publications
0
3
0
11
Order By: Relevance
“…Studying the performance of drippers subjected to critical conditions of water quality, Ribeiro et al (2012) observed that the models of pressure-compensating drippers showed variable performance with respect to the susceptibility to clogging. Such operational variation of the emitters is correlated with the architecture of each dripper: length, shape and dimensions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying the performance of drippers subjected to critical conditions of water quality, Ribeiro et al (2012) observed that the models of pressure-compensating drippers showed variable performance with respect to the susceptibility to clogging. Such operational variation of the emitters is correlated with the architecture of each dripper: length, shape and dimensions.…”
Section: Resultsmentioning
confidence: 99%
“…The maintenance of high uniformity of water application in irrigation systems becomes fundamental for an efficient irrigation regarding the use of water resources and reduction of costs (Ribeiro et al, 2012). However, due to the presence of physical, chemical and biological agents in the sewage effluent, the drippers are susceptible to alterations in the flow rate and reduction in the application uniformity.…”
Section: Introductionmentioning
confidence: 99%
“…A qualidade de água afeta negativamente o coeficiente de uniformidade e de vazão principalmente de gotejadores (RIBEIRO et al, 2012).…”
Section: Parâmetrosunclassified
“…Diversos tipos de gotejadores estão disponíveis no mercado, apresentando diferentes sensibilidades ao entupimento, fato que pode ser verificado em trabalhos realizados por Ribeiro et al (2012) e Cunha et al (2013). Esse inconveniente advém de causas biológicas, físicas e/ou químicas, ocorrendo todos conjuntamente quando se utilizam águas com elevados valores de ferro, bactéria e material orgânico (RAVINA et al, 1992).…”
Section: Introductionunclassified